2018
DOI: 10.4103/ejim.ejim_42_18
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertensive colopathy in Egyptian cirrhotic patients: an endoscopic study

Abstract: Background Hepatitis C virus (HCV) infection is a major health problem in Egypt. It is often complicated by liver cirrhosis and portal hypertension, resulting in gastroesophageal varices, gastropathy, and colopathy. However, there is still lack of data with respect to the prevalence and clinical relevance of colopathy in this kind of liver disease. The aim of this study was to determine the prevalence of colopathic lesions in HCV-related cirrhotic patients, and to study their associations with the severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Regarding coagulation, liver and kidney function results, Shalaby et al [15] The study by Abd-Elsalam et al [16] found that the means albumin level was 3.16±0.63, mean bilirubin level was 2.18±2.1, and the mean INR was 1.42±0.43, these results were comparable to our findings.…”
Section: Indicators Of Ph Included Clinical Andsupporting
confidence: 89%
See 4 more Smart Citations
“…Regarding coagulation, liver and kidney function results, Shalaby et al [15] The study by Abd-Elsalam et al [16] found that the means albumin level was 3.16±0.63, mean bilirubin level was 2.18±2.1, and the mean INR was 1.42±0.43, these results were comparable to our findings.…”
Section: Indicators Of Ph Included Clinical Andsupporting
confidence: 89%
“…In the current study, the age ranged from 55 to 77 years with a mean age ±SD was 68.50± 6.61 years, with male sex predominance [72% were males]. Shalaby et al [15] studied portal hypertensive colopathy in Egyptian cirrhotic patients. They performed a cross-sectional study with the inclusion of 60 patients with liver cirrhosis.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations